Anaerobic Biodegradability of Agricultural Renewable Fibers. (10th October 2013) - Shi, Bo; Lortscher, Peter; Palfery, Doris
Abstract : Natural fiber-based paper and paperboard products are likely disposed of in municipal wastewater, composting, or landfill after an intended usage. However, there are few studies reporting anaerobic sludge digestion and biodegradability of agricultural fibers although the soiled sanitary products, containing agricultural fibers, are increasingly disposed of in municipal wastewater or conventional landfill treatment systems, in which one or more unit operations are anaerobic digestion. We conducted a series of biodegradation studies using corn stalk and wheat straw pulp fibers to elucidate biodegradability and biodegradation kinetics under anaerobic sludge digestion conditions. The degradation results indicate that corn stalk achieved 78.4% biodegradation and wheat straw 72.4% biodegradation, all within 56 days of the study. In comparison, corn stalk generated more biogas than wheat straw. Unlike any raw agricultural crop residues, anaerobic biodegradation of agricultural fibers is largely unaffected by the presence of lignin, physical sizes of crop stalks, and plant cell wall constitutes.